ASA 2021 Statistics and Information Systems for Policy Evaluation Book of short papers of the opening conference - Bertaccini, Bruno; Fabbris, Luigi; Petrucci, Alessandra (Proceedings e report, 2021)
This book includes 25 peer-reviewed short papers submitted to the Scientific Opening Conference titled "Statistics and Information Systems for Policy Evaluation", aimed at promoting new statistical methods and applications for the evaluation of policies and organized by the Association for Applied Statistics (ASA) and the Department of Statistics, Computer Science, Applications DiSIA "G. Parenti" of the University of Florence, jointly with the partners AICQ (Italian Association for Quality Culture), AICQ-CN (Italian Association for Quality Culture North and Centre of Italy), AISS (Italian Academy for Six Sigma), ASSIRM (Italian Association for Marketing, Social and Opinion Research), Comune di Firenze, the SIS - Italian Statistical Society, Regione Toscana and Valmon - Evaluation & Monitoring.